Perubahan Kombinasi Bisnis Implementasi Dan Dampak PSAK 22 Terhadap Kinerja Keuangan Perusahaan - Silmi Humaira Harahap; Suci Ralita Lestari; Naufal Fauzan Hsb; Bana Ahmad Gautama (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
Using a literature research methodology, this paper investigates how business combination accounting was implemented both before and after PSAK 22, which is now known as PSAK 103 on Business Combinations. This research analyzes profit margin, return on equity (ROE), and return on assets (ROA) to assess the impact of PSAK 22 on the business's financial performance. Prior to PSAK 22, businesses often employed the "purchase method" or "pooling of interest." Results from prior research indicate that ROA, ROE, and profit margins are significantly impacted by business combinations. Although financial performance is frequently improved by mergers and acquisitions, the outcomes differ among industries. This article requires a broader range of information in order to function as a reference for future study on business combinations with PSAK 22/103 case studies and more diverse variables.